Peningkatan Fasilitas Bagi Tahfizh Anak Usia Dini â€œKuttab Rumah Quranâ€ Menuju Persaingan Pendidikan Anak Pra Sekolah - Aristanto, Eko; Hidayatullah, Syarif; Rachmawati, Ike Kusdyah; Waris, Abdul; Khalikussabir, Khalikussabir (University of Islam Malang, 2020)
Tahfizh Anak Usia Dini Kuttab Rumah Quran (TAUD KRQ) is an educational institution that concentrates on educating Quran from the early age.Â TAUD is a tahfidz program for the 3-6 years old children, enjoyable activities with the Quran is the approach. The expectation of this program is they would have kind of passion and good at memorizing the Quran, so that one day he would become Hamilul Quran, Insya Allah. TAUD KRQ in its implementation to create hafiz (memorizers) of the Quran ideally should have learning facilities and a balanced playing considering TAUD students are the early childhood who are still love to play. To achieve these ideal conditions, TAUD KRQ requires the cooperation from various parties.Â The reforms that must be equipped to achieve goals are the improvement of indoor and outdoor learning facilities, information media and motivational instructor. By the Observation, Survey, consultation, training, discussion, andÂ direct practice method, the results of community service activities are as follows: 1) Issues the aspects of outdoor facilities are assisted by repairing playgrounds, building condition with colors that match as bright and colorful, 2) Issues of Indoor facilities are assisted with the provision of Learning Media like 2 pieces of magnetic blackboard, printers, puzzle games, 20 writing tables and puzzle rugs to play on the floor.Â 3) Issues human resources are assisted by conducting motivational training for administrators and teachers, 4) Issues of marketing are assisted by creating a Blog.